2021
DOI: 10.47836/pjssh.29.2.33
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Vocabulary Learning Strategies of Discovery and Consolidation in Malaysian Primary School English Language Classrooms

Abstract: A good grasp of vocabulary enables language learners to articulate, comprehend and communicate ideas and concepts effectively. For learners whose first language is not English, mastering vocabulary knowledge in terms of the breadth and depth is challenging and needs to start at a young age through the use of various strategies. The lack of English language vocabulary knowledge would demotivate learners and even result in abandoning efforts to learn the language. Therefore, it is important that learners know an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…By reading too, learners can improve their experiences, develop new insights, solve problems, and elevate their critical thinking. When learners read a text, the results of reading activities can underpin their writing skills and develop their vocabulary and grammar (Rohmah, 2018;Ambarini et al, 2018;Kho et al, 2021;Nayan & Krishnasamy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…By reading too, learners can improve their experiences, develop new insights, solve problems, and elevate their critical thinking. When learners read a text, the results of reading activities can underpin their writing skills and develop their vocabulary and grammar (Rohmah, 2018;Ambarini et al, 2018;Kho et al, 2021;Nayan & Krishnasamy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that primary school students preferred to use cognitive strategies as these strategies involve a mechanical approach to learning new vocabulary by translating, memorizing and listing words. Another suggestion made by the study was that primary school students' preference toward cognitive strategies in vocabulary learning is due to a high perception of memory retention in learning vocabulary (Kho et al, 2021(Kho et al, , p.1391.…”
Section: Research In Vls Among Secondary School Studentsmentioning
confidence: 99%
“…Intending to explore the VLS among 132 primary school students in Sarawak, Malaysia, Kho et al (2021) gathered data using a survey and interview. The survey items were based on Oxford's VLS classifications.…”
Section: Research In Vls Among Secondary School Studentsmentioning
confidence: 99%
“…The role of vocabulary cannot be neglected in language learning. It is central to language acquisition whether the language being learned is first, second, or foreign (Khan et al, 2018;Kho, Ramanair, & Pandian, 2021). Richards and Renandya (2002) stated that vocabulary is an important core of language proficiency.…”
Section: Introductionmentioning
confidence: 99%